Group testing against Covid-19 - Christian Gollier; Olivier Gossner (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
It is well-known that group testing is an efficient strategy to screen for the presence of a virus. It consists in pooling n individual samples with a single test using RT-PCR. If at least one individual is infected, the test is positive, and it is negative otherwise. We show how group testing can be optimized in three applications to multiply the efficiency of tests against Covid-19: Estimating virus prevalence to measure the evolution of the pandemic; bringing negative groups back to work to exit the current lockdown; and testing for individual infectious status to treat sick people. For an infection level around 2%, group testing could multiply the power of testing by a factor 20. The implementation of this strategy in the short run requires limited investments and could bypass the current immense shortage of testing capacity.
Keywords: 330; Coronavirus; Experiment; Kohortenanalyse; Theorie